(untitled) (Jurnal Simki Economic, 2025)
This study aims to analyze the influence of Skin Health Concerns, Masculinity, Perception Regarding Skincare, Social Media Use, and Self-Image Concerns on Men’s Skincare Purchase Intention in Gen Z Men in Jabodetabek. This study uses a quantitative approach with an online survey method through a questionnaire. The population is Generation Z men aged between 15-28 years in the Jabodetabek area and samples were collected from 174 respondents who have experience using skincare or not. The data analysis technique uses Covariance Based Structural Equation Modeling (CB-SEM) with the help of AMOS software. The results showed that Social Media Use has a positive effect on Self-Image Concerns, and Self-Image Concerns has a positive effect on Men’s Skincare Purchase Intention. However, the variables Skin Health Concerns, Masculinity, and Perception Regarding Skincare have no effect on Men’s Skincare Purchase Intention. Self-image formation through social media is the main factor that drives Gen Z men to buy skincare products. This finding contributes to the development of consumer behavior science, especially in the context of gender and self-care, and becomes the basis for skincare cosmetic companies to design marketing strategies that are more relevant and adaptive to modern male consumer trends.